1994
DOI: 10.1289/ehp.102-1566908
|View full text |Cite
|
Sign up to set email alerts
|

Human milk as a bioindicator for body burden of PCDDs, PCDFs, organochlorine pesticides, and PCBs.

Abstract: In the State Laboratory of North Rhine-Westphalia for Food, Pharmaceutical and Environmental Chemistry (Chemisches Landesuntersuchungsamt), more than 600 individual human milk samples have been analyzed for polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs), and more than 1400 individual milk samples have been analyzed for organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) since 1984. All samples were collected on a voluntary basis from nursing mothers mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…For example, Norén and Meironyte 31 in Sweden and Fü rst et al 32 in Germany reported that the milk levels of PCDDs, PCDFs and PCBs decreased dramatically from the early 1970s to the late 1990s. In contrast, Norén and Meironyte 31 reported a dramatic increase in milk levels of selected PBDE congeners over this period.…”
Section: Bm Biomonitoring Studiesmentioning
confidence: 99%
“…For example, Norén and Meironyte 31 in Sweden and Fü rst et al 32 in Germany reported that the milk levels of PCDDs, PCDFs and PCBs decreased dramatically from the early 1970s to the late 1990s. In contrast, Norén and Meironyte 31 reported a dramatic increase in milk levels of selected PBDE congeners over this period.…”
Section: Bm Biomonitoring Studiesmentioning
confidence: 99%
“…Both PCB-126 and the other CoPCBs are highly lipophilic and accumulated in animal and human organs [1,3,12,22]. Therefore, Co-PCBs may inhibit the function of the drug extrusion systems in many organs, as shown in this experiment.…”
Section: Discussionmentioning
confidence: 63%
“…Due to the food chain and bioaccumulation, these chemicals might have become highly accumulated in humans and animals [1,3,6,12,22]. It was considered that almost the toxic effects of Co-PCBs were initiated by binding with the aryl hydrocarbon receptor (AhR) [18,24], and these chemicals induced estrogenic and antiestrogenic responses via the crosstalk between AhR and estrogen receptor [8,31].…”
mentioning
confidence: 99%
“…In infants, their diet is even more restricted, often to a singular source. Numerous EDCs have been detected in both breast milk and infant formula samples; thus, dietary sources of exposure would be expected to be an important exposure pathway (8,(79)(80)(81)(82)(83). If the primary dietary source is contaminated, this may result in increased exposure in infants.…”
Section: Dietmentioning
confidence: 99%